Rainfed areas: poor definition and flawed solutions. Issue 2 (4th March 2018) - Kumar, M. Dinesh; Reddy, V. Ratna; Narayanamoorthy, A.; Bassi, Nitin; James, A. J.
Abstract: This article questions the criterion used by government of India to classify agricultural areas into 'rainfed' and 'irrigated', merely on the basis of percentage of area under irrigation, in spite of the vast differences in the biophysical and socio-economic characteristics between areas classified as 'rainfed'. This criterion fails to consider the agro-climate and hydro-meteorology of the area, which decide whether crops can be grown under rainfed conditions or require irrigation. Watershed development interventions, which are usually prescribed for agricultural development of rainfed areas, are bound to fail when rainfall is low and aridity is high, and strategically, interventions should be based on agro-ecology and hydro-meteorology.